PERAN SISTEM DIGITAL DALAM MENINGKATKAN KAPABILITAS MANAJERIAL TERHADAP EFEKTIVITAS MANAJEMEN STOK GUDANG BEKU IKAN - Harun AS; Muhammad Helmi; Isniar Budiarti; Dedi Sulistiyo; Siti Kurnia Rahayu (UM. Bengkulu, 2026)
Digital transformation has become a strategic necessity in fisheries supply chain management, especially in frozen fish warehouses that demand data accuracy, decision speed, and quality control on an ongoing basis. This article aims to analyze the role of digital systems in improving managerial capabilities on the effectiveness of fish frozen warehouse stock management. This study uses a qualitative approach based on literature study and conceptual analysis enriched with a philosophical perspective of science, especially the ontological, epistemological, methodological, axiological, and praxis-teleological dimensions. The results of the study show that digital systems not only function as operational tools, but also form a new reality in managerial practices that are socio-technical in nature. Through warehouse information systems, real-time data-based recordings, and the integration of monitoring technology, managers gain more adaptive, accurate, and responsive capabilities in managing stock. Managerial capabilities strengthened by digital systems contribute directly to improving the effectiveness of stock management, reducing recording errors, minimizing losses, and improving cold supply chain resilience. Teleologically, this transformation is directed at the creation of a sustainable, transparent, and competitive management system. Thus, the digital system is an important foundation in building a modern and strategic fish frozen warehouse stock management model.